STRUKTUR KOMUNITAS BULU BABI (Echinoidea) DI ZONA INTERTIDAL PERAIRAN MANOKWARI - Jenly Haurissa; Lutfi Lutfi; Abdul Hamid A. Toha (Jurnal Kelautan, 2021)
ABSTRACTSea urchins (Echinoidea) are spread from shallow intertidal areas to the deep sea. This study aims to determine species diversity and abundance of sea urchins in the intertidal zone of Manokwari Waters. The study took place in three locations in the intertidal zone of Manokwari waters. The method used was purposive sampling with a line transect sampling technique measuring 1x1 meter in size. We found 10 species namely H. mammilatus, E. mathaei, E. oblonga, E. viridis, E. lucunter, D. setosum, E. calamaris, D. savignyi, Echinotrix sp., and E. diadema. Sea urchin (H ') index value ranges from H’= 0.2173–0.448430; Index (E) ranges between 0.3108–0.7477 and the Index Value (C) ranges between 0.3769-0.7911 in each of the intertidal zones. L1 (Di = 0.5 ind / 6m2 - 21.8 ind / 6m2); KR = (2.0270%–88.5135%); L2 (Di = 0.5 ind / 6m2–9.5 ind / 6m2; KR = 0.8474% -48.3050%) and L3 (Di = 0.8 ind / 6m2–7.1 ind / 6m2; KR = 7.6923% -66.1538%).Keywords: Abundance, Intertidal, Manokwari, Sea Urchin, Species Diversity,ABSTRAKBulu babi (Echinoidea) tersebar di daerah pasang surut yang dangkal hingga laut dalam. Penelitian ini bertujuan untuk mengetahui keanekaragaman jenis dan kelimpahan bulu babi di zona intertidal. Penelitian dilakukan pada tiga lokasi di Perairan Manokwari. Metode yang digunakan adalah purposive sampling dengan teknik line transect sampling berukuran 1 × 1 meter. Kami menemukan 10 spesies yaitu H. mammilatus, E. mathaei, E. oblonga, E. viridis, E. lucunter, D. setosum, E. calamaris, D. savignyi, Echinotrix sp., dan E. diadema. Nilai indeks bulu babi (H') berkisar dari H' = 0,2173–0,448430; Indeks (E) berkisar antara 0,3108–0,7477 dan Nilai Indeks (C) berkisar antara 0,3769–0,7911. Kelimpahan mutlak dan relatif pada setiap lokasi adalah: L1 (Di = 0,5 ind/6m2 - 21,8 ind/6m2); KR = (2,0270% - 88,5135%); L2 (Di = 0,5 ind/6m2–9,5 ind/6m2; KR = 0,8474% -48.3050%) dan L3 (Di = 0,8 ind/6m2–7,1 ind/6m2; KR = 7.6923% -66,1538%).Kata Kunci: Bulu Babi, Intertidal, Keanekaragaman Jenis, Kelimpahan, Manokwari